4CPS-007 Interdisciplinary team in the follow-up of a patient with teduglutida. (2nd March 2018) - Bellver, M; Montero, M; Segui, I; Gil, R; Masia, V; Soler, E
Abstract : Background: Short bowel syndrome (SBS) results from the physical loss of portions of the intestines. These patients develop intestinal failure and they require external intravenous support. Teduglutide promotes changes at an intestinal level, favouring the growth of the mucosa and increasing absorption. There is reduced experience in the management of this treatment so it is necessary for an interdisciplinary team to carry out a specific, individualised and consensual follow-up. Purpose: Our objective is to analyse the results obtained by the interdisciplinary team in the follow-up of a patient with SBS, after the elaboration and implantation of a follow-up protocol with the active participation of the pharmacist. Material and methods: An interdisciplinary team was established between the Pharmacy, Digestive and Home Hospitalisation Units (HHU) for the follow-up of a 38-year-old patient with SBS. We held joint meetings to review documentation, and developed and agreed a protocol. Duration of the follow-up was 6 months. The digestologist monitored the patient monthly, the HHU doctor twice-weekly and the pharmacist bi-weekly. Pharmaceutical activity focused on the adjustment of nutritional support and fluid therapy according to agreed parameters such as diuresis, ostomy losses, analytical nutritional parameters and the safety of teduglutide. We also adjusted dietary measures weekly. Results: With the establishment of the interdisciplinary team, after seven meetings, we were able to agree on a follow-up protocol for the patient. PN and fluid contributions decreased by 53% and 38%, respectively. The contribution time was reduced from 15 hours a day 7 days a week, to 7 hours a day for 6 days. The initial supply was 1640 ml (10 g lipid, 200 g glucose, 11.22 g N) and reduced to 840 ml (4.97 g lipids, 99 g glucose, 5.7 g N). We have managed to maintain the nutritional status required by the patient. In addition, with this intervention we were able to improve the patient's quality of life, which we evaluated according to two scales: SF-36 and GiQLI. No adverse effects were detected. Conclusion: The role of the pharmacist in the interdisciplinary team, assuming an active and coordinating role at many times in the process, has contributed to achieving the therapeutic objectives and nutritional control of the patient. No conflict of interest